Consumer’s Perception Of Global Branding: Kopiko Product Placement In Korean Drama - Aulia Ecallypta, Saffa; Surayya Ulfa, Nurist; Qurrota Ayun, Primada (Interaksi Online, 2024)
The purpose of this study is to describe consumer perceptions of global branding using product placement strategies in Korean dramas. Qualitative research is a research method that provides descriptive data in the form of written or spoken words from individuals and the behavior of observed phenomena. The research "Consumer Perception of Global Branding: Kopiko Product Placement in Korean Drama" uses a qualitative descriptive approach. This method involves capturing and explaining consumers' perceptions and experiences about their opinions of Kopiko in Korean dramas. The result was that the product placement successfully increased brand exposure and strengthened the consumer experience with the identification of three distinct consumer perceptions. Despite the success, the study highlights the need for brand consistency and effective messaging, as well as the importance of emphasizing brand distinctive features such as the use of real coffee beans to reinforce identity and meet consumer expectations. Furthermore, cultural sensitivity to brand associations with Korean culture influences consumer perceptions, while Martin Roll's global branding theory provides insight into how factors such as brand recognition, unique value, consumer experience, consistency, and cultural sensitivity affect consumer perceptions